Preparation method of cobalt nitride nanowire rich in nitrogen vacancies and application of cobalt nitride nanowire in advanced treatment of antibiotic wastewater

By introducing nitrogen defects into cobalt nitride nanowires, the problem of insufficient adsorption capacity in advanced oxidation processes is solved, and efficient peracetic acid activation and pollutant degradation is achieved, which is suitable for deep treatment of antibiotic wastewater.

CN119702040AActive Publication Date: 2025-03-28SHANDONG UNIV

Patent Information

Application Number
CN202411880351.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The application of existing cobalt nitride in advanced oxidation processes is limited by its insufficient adsorption capacity to oxygen-containing substances and its inability to effectively enrich oxidants and pollutants, resulting in low catalytic reaction efficiency.

Method used

By doping metal in situ during the synthesis of cobalt nitride precursors, a large number of nitrogen defects are introduced to form cobalt nitride nanowires rich in nitrogen vacancies, improving their adsorption ability and catalytic activity on oxygen-containing substances.

Benefits of technology

The peracetic acid activation efficiency and pollutant degradation ability of the cobalt nitride catalyst are significantly improved, and efficient antibiotic wastewater treatment is achieved, and good pH tolerance and environmental adaptability are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005198054620000011
    Figure HDA0005198054620000011
  • Figure HDA0005198054620000012
    Figure HDA0005198054620000012
  • Figure HDA0005198054620000021
    Figure HDA0005198054620000021
Patent Text Reader

Abstract

The invention relates to a preparation method of cobalt nitride nanowires rich in nitrogen vacancies and application of the cobalt nitride nanowires in advanced treatment of antibiotic wastewater. A large number of nitrogen defects are introduced into cobalt nitride through a metal doping method, the adsorption capacity of cobalt nitride on oxygen-containing substances is enhanced, and the main difficult problem restricting application of cobalt nitride in an advanced oxidation process is solved. The catalytic material shows huge application potential in a peracetic acid activation process, and the activation efficiency of peracetic acid and the degradation efficiency of pollutants within 5 min can reach 100%. In addition, the introduction of the nitrogen defect effectively regulates and controls the generation of the selective oxide Co (IV) = O in the process, and the selective removal of pollutants can be realized. And the strain also shows extremely strong pH tolerance and environmental background resistance, and is more suitable for actual wastewater treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of cobalt nitride nanowires rich in nitrogen vacancies and application of the nanowires in deep treatment of antibiotic wastewater, belonging to the field of new materials and environmental technology. Background Art

[0002] In recent years, trace organic pollutants such as environmental endocrine disruptors, drugs, and personal care products have been frequently detected in the environment. These organic substances pose a serious threat to water quality, the environment, and human health. Advanced oxidation processes are effective technologies for degrading trace organic pollutants, such as persulfate and hydrogen peroxide activation technology. Among them, peracetic acid (PAA) with good oxidation, disinfection, and sterilization functions has attracted more and more attention from researchers. The dissociation energy of the OO bond of peracetic acid (159 kJ mol -1 ) is much lower than hydrogen peroxide (213 kJ mol -1 ) and persulfate (317 kJ mol -1 ), peracetic acid can be activated more efficiently through various methods such as ultraviolet light, ultrasound, metal ions and heterogeneous catalysts to produce various active oxygen species, such as hydroxyl radicals (·OH) and organic radicals (RO·). However, these activation technologies have problems such as high cost, high energy consumption and serious secondary pollution, which seriously affect the stable and long-term operation of wastewater purification systems. Therefore, it is urgent to develop efficient, green and economical peracetic acid activation catalysts.

[0003] Transition metal nitrides have shown great advantages in the field of catalysis due to their unique electronic structure, high conductivity and acid-base chemical stability. Compared with common transition metal oxides, transition metal nitrides show more significant metallic properties, and nitrogen atoms occupy the interstitial positions of their metal structure, affecting the local electronic structure and changing the nature of chemical reactions. On the one hand, they provide reactants and products with adsorption strength similar to that of precious metals. On the other hand, the bonding between metal and nitrogen can promote more efficient electron transfer, making it have higher conductivity efficiency, and reduce the d-band electronic center, further improving the catalyst activity.

[0004] At present, cobalt nitride is mainly used in the field of photocatalysis and electrocatalysis, while the exploration and research on advanced oxidation processes has not yet been carried out. The difficulty lies mainly in the limited adsorption capacity of cobalt nitride for oxygen-containing substances, which cannot well enrich oxidants and pollutants on the surface and trigger the occurrence of catalytic reactions. Introducing nitrogen defects into catalysts is an effective means to solve this problem. In addition, defect engineering can also adjust the electronic structure, reduce the activation energy barrier, and enhance electron transfer at the interface. At present, the commonly used methods for constructing defects include doping, reduction, etching, ball milling, plasma, etc. Among them, the method of introducing defects by lattice doping has the advantages of low cost, green, pollution-free, high stability, etc., and can achieve precise control of material structure. However, due to the special bonding mode and crystal structure in metal nitrides, lattice doping of metal ions on their matrix is ​​difficult to achieve.

[0005] Therefore, by introducing a large number of nitrogen defects into cobalt nitride through new low-cost, green and environmentally friendly means and applying them to advanced oxidation processes, ultra-efficient activation of peracetic acid and ultra-fast degradation of pollutants were achieved, which is of great significance to the degradation of pollutants. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a method for preparing cobalt nitride nanowires rich in nitrogen vacancies and application thereof in deep treatment of antibiotic wastewater. Summary of the invention:

[0008] The present invention introduces a large number of nitrogen defects into the cobalt nitride nanowires by in-situ doping metals during the synthesis of the cobalt nitride precursor, and applies it to the advanced oxidation process for the first time. The construction of nitrogen defects effectively enhances the adsorption capacity of the catalyst for oxygen-containing species, promotes its enrichment of oxidants, and effectively solves the difficult problems that traditionally restrict the application of metal nitride in the advanced oxidation process. The material shows ultra-efficient peracetic acid utilization and pollutant removal rate in the peracetic acid-based advanced oxidation process, and can well resist the interference of the actual environmental background, and has great potential for practical application. In addition, the entire preparation process has easy-to-obtain raw materials, low cost, and simple operation, which is conducive to industrial-scale production.

[0009] The technical solution of the present invention is as follows:

[0010] A method for preparing cobalt nitride nanowires rich in nitrogen vacancies comprises the following steps:

[0011] (1) Dissolve Co(NO3)2, NH4F and CO(NH2)2 in water, add metal salt solution, stir evenly and perform hydrothermal reaction, wash with ethanol and water after cooling, and dry to obtain metal-doped Co(CO3) 0.5 (OH)·0.11H2O precursor;

[0012] (2) Metal doping Co(CO3) 0.5 The (OH)·0.11H2O precursor was heated and calcined in an ammonia atmosphere, and the cobalt nitride nanowire material rich in nitrogen vacancies was prepared by an ammonia pyrolysis method.

[0013] Preferably according to the present invention, in step (1), the molar ratio of Co(NO3)2, NH4F and CO(NH2)2 is 1:(1-5):(4-10).

[0014] More preferably, in step (1), the molar ratio of Co(NO3)2, NH4F and CO(NH2)2 is 1:2:5.

[0015] Preferably according to the present invention, in step (1), the volume ratio of the molar amount of Co(NO3)2 to water is (1-3):(20-40), unit, mmol / mL.

[0016] Preferably according to the present invention, in step (1), the metal salt solution is one of Cu(NO3)2 solution, Mn(NO3)2 solution and Ni(NO3)2 solution.

[0017] Most preferably, in step (1), the metal salt solution is a Mn(NO3)2 solution.

[0018] Further preferably, in step (1), the concentration of the metal salt solution is 0.05-0.3 mol / L, and the molar ratio of the metal salt to Co(NO3)2 in the metal salt solution is (0-0.13):1.

[0019] Most preferably, in step (1), the molar ratio of the metal salt to Co(NO3)2 in the metal salt solution is 0.07:1.

[0020] Preferably according to the present invention, in step (1), the hydrothermal reaction temperature is 110-130° C., and the hydrothermal time is 4-8 h.

[0021] Preferably according to the present invention, in step (1), washing with ethanol and water refers to washing with ethanol and water alternately by centrifugation three times each.

[0022] Preferably according to the present invention, in step (1), the drying is performed at 50-70° C. for 10-16 hours.

[0023] Preferably according to the present invention, in step (2), the heating rate of the calcination is 4-10°C / min.

[0024] Preferably according to the present invention, in step (2), the heating calcination temperature is 400-500° C., and the calcination time is 100-160 min.

[0025] Further preferably, in step (2), the heating calcination temperature is 460°C and the calcination time is 120 min.

[0026] Preferably, in step (2), the ammonia flow rate is 300-600 sccm, and the sample is removed and ground into powder and passed through a 100-mesh sieve.

[0027] A cobalt nitride nanowire rich in nitrogen vacancies is prepared by the method.

[0028] The application of the above-mentioned cobalt nitride nanowires rich in nitrogen vacancies in the deep treatment of antibiotic wastewater.

[0029] Preferably, the specific application method according to the present invention has the following steps: at room temperature, adding a cobalt nitride catalyst rich in nitrogen vacancies and peracetic acid to a pollutant solution, and stirring to carry out a catalytic degradation reaction.

[0030] Preferably according to the present invention, the pollutant is an antibiotic or a phenolic pollutant, the pollutant concentration is 15-35 μmol / L, and the pH of the pollutant solution is 3-11.

[0031] Preferably according to the present invention, the dosage of the catalyst is 0.01-0.2 g / L.

[0032] Most preferably, the dosage of the catalyst is 0.05 g / L.

[0033] Preferably according to the present invention, the dosage of peracetic acid is 100-400 μmol / L.

[0034] Most preferably, the dosage of peracetic acid is 200 μmol / L.

[0035] The beneficial effects of the present invention are:

[0036] 1. The raw materials selected in the present invention are easily available and low in cost. Through simple in-situ metal doping, the controllable construction of nitrogen defects in cobalt nitride materials is achieved, thereby further improving its catalytic activity.

[0037] 2. The present invention significantly improves the adsorption efficiency of the cobalt nitride catalyst for oxygen-containing substances by introducing nitrogen defects into the catalyst, thereby enhancing its ability to activate peracetic acid and achieving ultra-efficient degradation of organic pollutants. In addition, the introduction of nitrogen defects also enhances the high selectivity for active oxygen species, which is more conducive to the selective degradation of pollutants.

[0038] 3. The PAA activated system of cobalt nitride nanowires rich in nitrogen vacancies prepared by the present invention has strong pH tolerance and can effectively resist the influence of the natural environment background, showing great potential in the treatment of actual wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 XRD spectra of cobalt nitride containing different nitrogen vacancies prepared in Examples 1, 2, 3, 4 of the present invention and Comparative Example 1.

[0040] Figure 2 XPS spectra of cobalt nitride containing different nitrogen vacancies prepared in Examples 1, 2, 3, 4 of the present invention and Comparative Example 1.

[0041] Figure 3 EPR spectra of cobalt nitride containing different nitrogen vacancies prepared in Example 1 and Comparative Example 1 of the present invention.

[0042] Figure 4 This is a comparison chart of the efficiency of activating peracetic acid by cobalt nitride containing different nitrogen vacancies prepared in Examples 1, 2, 3, 4 of the present invention and Comparative Example 1.

[0043] Figure 5 This is a comparison chart of the performance of cobalt nitride containing different nitrogen vacancies prepared in Examples 1, 2, 3, 4 of the present invention and Comparative Example 1 in activating peracetic acid to degrade sulfonamide.

[0044] Figure 6 The effects of different cobalt nitrides containing different nitrogen vacancies prepared in Examples 1, 2, 3, 4 of the present invention and Comparative Example 1 on the PMSO consumption, PMSO2 generation and PMSO2 generation rate activated with peracetic acid.

[0045] Figure 7 The effect of different catalyst dosages on the degradation performance of sulfonamide and methoxazole.

[0046] Figure 8 This is the effect of different peracetic acid dosages on the degradation performance of sulfonamide and methoxazole.

[0047] Fig. 9 The effect of different pH on the degradation performance of sulfonamide and methoxazole.

[0048] Fig.10 The effect of different coexisting anions on the degradation performance of sulfonamide and methoxazole. DETAILED DESCRIPTION

[0049] The present invention will be further described below through specific embodiments in conjunction with the accompanying drawings, but is not limited thereto.

[0050] The raw materials used in the examples are all conventional commercially available products.

[0051] Embodiment 1,

[0052] A method for preparing cobalt nitride nanowires rich in nitrogen vacancies, comprising the following steps:

[0053] (1) 1.5 mmol Co(NO3)2, 3 mmol NH4F and 7.5 mmol CO(NH2)2 were dissolved in 30 mL of water by stirring, and then 1 mL of 0.1 mol / L Mn(NO3)2 solution was added and mixed evenly;

[0054] (2) The solution obtained in step (1) was transferred to a hydrothermal reactor and subjected to hydrothermal reaction at 120° C. for 5 h. After cooling, the sample was taken out and washed alternately with ethanol and water for 3 times each. The obtained solid sample was placed in an oven and dried at 60° C. for 12 h.

[0055] (3) The sample obtained after drying in step (2) is placed in a tubular furnace, and heated to 450°C at a heating rate of 5°C / min in an ammonia atmosphere, and calcined at 450°C for 120 min. After naturally cooling to room temperature, the sample is taken out, ground and sieved to obtain a cobalt nitride catalyst rich in nitrogen vacancies, which is recorded as Co4N / CoN-1Mn.

[0056] Application in deep treatment of antibiotic wastewater:

[0057] 5 mg of the nitrogen vacancy-rich cobalt nitride catalyst synthesized in step (3) was added to 100 mL of simulated wastewater (pH = 7) with a sulfonamide-p-methoxazole concentration of 20 μmol / L, and then 200 μL of 0.1 mol / L peracetic acid solution was added to trigger the catalytic reaction;

[0058] During the reaction, samples were taken at certain time intervals, and the active substances in the samples were quenched with 0.05 mol / L Na2S2O3. The concentrations of the samples were then measured using high performance liquid chromatography.

[0059] Embodiment 2,

[0060] The preparation method is the same as that described in Example 1, except that in step (1), the volume of the 0.1 mol / L Mn(NO3)2 solution added is 0.5 mL, and the remaining operations and dosages are exactly the same as those in Example 1. The obtained catalyst is recorded as Co4N / CoN-0.5Mn.

[0061] Embodiment 3,

[0062] The preparation method is the same as that described in Example 1, except that in step (1), the volume of the 0.1 mol / L Mn(NO3)2 solution added is 1.5 mL, and the remaining operations and dosages are exactly the same as those in Example 1. The obtained catalyst is recorded as Co4N / CoN-1.5Mn.

[0063] Embodiment 4,

[0064] The preparation method is the same as that described in Example 1, except that in step (1), the volume of the 0.1 mol / L Mn(NO3)2 solution added is 2 mL, and the remaining operations and dosages are exactly the same as those in Example 1. The obtained catalyst is recorded as Co4N / CoN-2Mn.

[0065] Comparative Example 1

[0066] The preparation method is as described in Example 1, except that in step (1), no Mn(NO3)2 solution is added, and the remaining operations and amounts are exactly the same as those in Example 1. The obtained catalyst is recorded as Co4N / CoN.

[0067] Experimental Example 1

[0068] The XRD patterns of the cobalt nitride catalysts prepared in Examples 1, 2, 3, 4 and Comparative Example 1 are as follows: Figure 1 As shown. Figure 1 It can be seen that the CoN / Co4N composite material was successfully synthesized. And the manganese doping did not affect the structural species of the material, indicating that its doping was extremely trace.

[0069] The XPS graphs of the cobalt nitride catalysts prepared in Examples 1, 2, 3, 4 and Comparative Example 1 are as follows: Figure 2 As the amount of manganese doping increases, Co 3+ The peak shifts toward higher binding energies, which can be attributed to the increased degree of electron delocalization of Co atoms, confirming that the electronic structure is significantly affected by Mn doping.

[0070] The EPR spectra of the cobalt nitride catalyst prepared in Example 1 and Comparative Example 1 are as follows: Figure 3 As shown. Mn doping significantly increases the nitrogen vacancies in cobalt nitride materials.

[0071] Experimental Example 2

[0072] Examples 1, 2, 3, 4 and Comparative Example 1 with different doping amounts of Mn 2+ Comparison of the performance of peracetic acid on catalyst activation Figure 4 As shown in Figure 2, the activation efficiency of peracetic acid increased significantly with the increase of manganese doping amount, which proves the important role of nitrogen defects in the activation process of peracetic acid.

[0073] Experimental Example 3

[0074] Examples 1, 2, 3, 4 and Comparative Example 1 with different doping amounts of Mn 2+ Comparison of the performance of catalysts activated with peracetic acid for pollutant degradation Figure 5As shown in the figure, with the increase of manganese doping, the removal efficiency of sulfonamide on methoxazole was significantly improved, indicating that nitrogen deficiency promoted the activation of peracetic acid to produce more active substances to degrade pollutants.

[0075] Experimental Example 4

[0076] Benzyl sulfoxide (PMSO) was used as a probe for high-metal substances. The ability of PMSO to generate PMSO2 by oxygen atom transfer between high-valent metals was used to explore the effects of different doping levels of Mn 2+ Effect of high-valent cobalt production during catalyst activation with peracetic acid. Figure 6 The different doping amounts of Mn in Examples 1, 2, 3, 4 and Comparative Example 1 are shown in FIG. 2+ Experimental results on the effect of catalyst activation peracetic acid on PMSO conversion. The results show that with the increase of Mn 2+ With the increase of doping amount, the concentration of nitrogen vacancies in the catalyst increases, and the conversion rate of PMSO to PMSO2 also increases significantly, indicating that the introduction of nitrogen defects promotes the ability of the catalyst to activate peracetic acid to selectively produce Co(IV)=O.

[0077] Comparative Example 2

[0078] The same as the use of activated peracetic acid to remove pollutants in water as described in Example 1, except that:

[0079] The added mass of the catalyst was 0 mg, and the other operations and dosages were exactly the same as those in Example 1.

[0080] Comparative Example 3

[0081] The same as the use of activated peracetic acid to remove pollutants in water as described in Example 1, except that:

[0082] The added mass of the catalyst was 10 mg, and the other operations and dosages were exactly the same as those in Example 1.

[0083] Comparative Example 4

[0084] The same as the use of activated peracetic acid to remove pollutants in water as described in Example 1, except that:

[0085] The added mass of the catalyst was 20 mg, and the other operations and dosages were exactly the same as those in Example 1.

[0086] Experimental Example 5

[0087] Effects of different nitrogen vacancy-rich cobalt nitride catalytic dosages on the degradation of pollutants by active peracetic acid Figure 7When the catalyst dosage is 0.05 g / L, the pollutants can be completely removed within 5 minutes. When the catalyst dosage exceeds 0.05 g / L, its removal efficiency of pollutants decreases, which may be due to the fact that excessive catalyst addition may cause catalyst agglomeration to shield some active sites.

[0088] Comparative Example 5

[0089] The same as the use of activated peracetic acid to remove pollutants in water as described in Example 1, except that:

[0090] The added mass of 0.1 mol / L peracetic acid solution was 0 μL, and the other operations and dosages were exactly the same as those in Example 1.

[0091] Comparative Example 6

[0092] The same as the use of activated peracetic acid to remove pollutants in water as described in Example 1, except that:

[0093] The added mass of 0.1 mol / L peracetic acid solution was 100 μL, and the other operations and dosages were exactly the same as those in Example 1.

[0094] Comparative Example 7

[0095] The same as the use of activated peracetic acid to remove pollutants in water as described in Example 1, except that:

[0096] The added mass of 0.1 mol / L peracetic acid solution was 300 μL, and the other operations and dosages were exactly the same as those in Example 1.

[0097] Experimental Example 6

[0098] Effects of different peracetic acid dosages on the degradation of pollutants by active peracetic acid Figure 8 As shown in the figure, when the dosage of peracetic acid gradually increased, the system produced more active species, resulting in a significant increase in the removal rate of sulfonamide to methoxazole.

[0099] Experimental Example 7

[0100] As described in Example 1, the difference is that in step (4), the pH of the simulated wastewater is adjusted to 3, 5, 9, and 11, and the remaining operations and amounts are exactly the same as in Example 1.

[0101] Effects of different pH values ​​on the degradation of pollutants by active peracetic acid Fig. 9 The oxidation system can effectively remove pollutants in a wide pH range (3-11).

[0102] Embodiment 8,

[0103] As described in Example 1, the difference is that in step (4), various anions (Cl - 、HCO3 - 、H2PO4 - 、NO3 - 、SO4 2- ), and the rest of the operations and dosages are exactly the same as those in Example 1.

[0104] Fig.10 The effects of different coexisting anions on the degradation of pollutants by the oxidation system are shown. The oxidation system can well resist the interference of various coexisting anions, indicating that it is suitable for the removal of pollutants in actual water bodies.

Claims

1. A method for preparing cobalt nitride nanowires rich in nitrogen vacancies, comprising the following steps: (1) Dissolve Co(NO3)2, NH4F and CO(NH2)2 in water, add metal salt solution, stir evenly and perform hydrothermal reaction, wash with ethanol and water after cooling, and dry to obtain metal-doped Co(CO3) 0.5 (OH)·0.11H2O precursor; (2) Metal doping Co(CO3) 0.5 The (OH)·0.11H2O precursor was heated and calcined in an ammonia atmosphere, and the cobalt nitride nanowire material rich in nitrogen vacancies was prepared by an ammonia pyrolysis method.

2. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of Co(NO3)2, NH4F and CO(NH2)2 is 1:(1-5):(4-10), and the volume ratio of the molar amount of Co(NO3)2 to water is (1-3):(20-40), unit, mmol / mL.

3. The preparation method according to claim 1, characterized in that: In step (1), the metal salt solution is one of Cu(NO3)2 solution, Mn(NO3)2 solution, and Ni(NO3)2 solution, the concentration of the metal salt solution is 0.05-0.3 mol / L, and the molar ratio of the metal salt to Co(NO3)2 in the metal salt solution is (0-0.13):

1. Preferably, the molar ratio of the metal salt to Co(NO3)2 in the metal salt solution is 0.07:

1.

4. The preparation method according to claim 1, characterized in that: In step (1), the hydrothermal reaction temperature is 110-130° C., and the hydrothermal time is 4-8 hours.

5. The preparation method according to claim 1, characterized in that: Washing with ethanol and water means washing with ethanol and water alternately by centrifugation three times each, and drying means drying at 50-70° C. for 10-16 hours.

6. The preparation method according to claim 1, characterized in that: In step (2), the heating rate of the heating calcination is 4-10°C / min, the heating calcination temperature is 400-500°C, and the calcination time is 100-160min.

7. The preparation method according to claim 1, characterized in that: In step (2), the heating calcination temperature is 460° C., the calcination time is 120 min, the ammonia flow rate is 300-600 sccm, and after removing the sample, it is ground into powder and passed through a 100 mesh sieve.

8. A cobalt nitride nanowire rich in nitrogen vacancies, prepared by the method according to any one of claims 1 to 7.

9. Use of the cobalt nitride nanowires rich in nitrogen vacancies as claimed in claim 8 in deep treatment of antibiotic wastewater.

10. The use according to claim 8, characterized in that: The specific application method and steps are as follows: at room temperature, adding a cobalt nitride catalyst rich in nitrogen vacancies and peracetic acid to a pollutant solution, stirring to carry out a catalytic degradation reaction; The pollutants are antibiotics or phenolic pollutants, the pollutant concentration is 15-35 μmol / L, the pH value of the pollutant solution is 3-11, the dosage of the catalyst is 0.01-0.2 g / L, and the dosage of the peracetic acid is 0.1-400 μmol / L.

Citation Information

Patent Citations

  • Transition metal doped Co4N nanometer combustion catalyst and preparation method thereof

    CN115624984A

  • Cobalt-nitrogen-sulfur co-doped porous carbon nitride nanosheet and application of cobalt-nitrogen-sulfur co-doped porous carbon nitride nanosheet in photocatalytic production of H2O2

    CN118513064A

  • Preparation and application of Co-Nx co-doped carbon nanotube for in-situ encapsulation of cobalt nanoparticles

    CN118925704A

  • Method for treating antibiotic wastewater and eliminating biotoxicity by coupling piezoelectric catalysis with peracetic acid activation

    CN119874007A

  • Haber-bosch catalyst comprising an anion-vacant lattice

    US20210114005A1

Cited By

  • Preparation method of asymmetric nitrogen vacancy catalyst for electrochemical treatment of phenolic wastewater

    CN121222460A